Better Targeting, Better Efficiency for Wide-Scale Neuronal Transduction with the Synapsin Promoter and AAV-PHP.B - Jackson, Kasey L.; Dayton, Robert D.; Deverman, Benjamin E.; Klein, Ronald L. (Frontiers in Molecular Neuroscience, 2016)
Widespread genetic modification of cells in the central nervous system (CNS) with a viral vector has become possible and increasingly more efficient. We previously applied an AAV9 vector with the cytomegalovirus/chicken beta-actin hybrid (CBA) promoter and achieved wide-scale CNS transduction in neonatal and adult rats. However, this method transduces a variety of tissues in addition to the CNS. Thus we studied intravenous AAV9 gene transfer with a synapsin promoter to better target the neurons. We noted in systematic comparisons that the synapsin promoter drives lower level expression than does the CBA promoter. The engineered AAV-PHP.B serotype was compared with AAV9, and AAV-PHP.B did enhance the efficiency of expression. Combining the synapsin promoter with AAV-PHP.B could therefore be advantageous in terms of combining two refinements of targeting and efficiency. Wide-scale expression was used to model a disease with widespread pathology. Vectors encoding the amyotrophic lateral sclerosis (ALS)-related protein TDP-43 with the synapsin promoter and AAV-PHP.B were used for efficient CNS-targeted TDP-43 expression. Intracerebroventricular injections were also explored to limit TDP-43 expression to the CNS. The neuron-selective promoter and the AAV-PHP.B enhanced gene transfer and ALS disease modeling in adult rats.